Terahertz Photonics: Efficient Gap‐Free Broadband Terahertz Generators Based on New Organic Quinolinium Single Crystals (Advanced Optical Materials 21/2019). Issue 21 (4th November 2019) - Shin, Myeong‐Hoon; Kim, Won Tae; Kim, Se‐In; Lee, Seung‐Heon; Yu, In Cheol; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract : In article number 1900953, O‐Pil Kwon, Fabian Rotermund and co‐workers report that organic nonlinear optical crystals based on non‐planar anions with strongly electronegative and orthogonally oriented trifluoromethoxy groups exhibit enhanced macroscopic nonlinear optical response compared to conventional planar anions and show efficient gap‐free broadband THz wave generation.